Single-cell transcriptomic landscapes of the otic neuronal lineage at multiple early embryonic ages - Yuwei Sun; Luyue Wang; Tong Zhu; Bailin Wu; Guangqin Wang; Zhengnan Luo; Chao Li; Wu Wei; Zhiyong Liu (Cell Reports, 2022)
Summary: Inner ear vestibular and spiral ganglion neurons (VGNs and SGNs) are known to play pivotal roles in balance control and sound detection. However, the molecular mechanisms underlying otic neurogenesis at early embryonic ages have remained unclear. Here, we use single-cell RNA sequencing to reveal the transcriptomes of mouse otic tissues at three embryonic ages, embryonic day 9.5 (E9.5), E11.5, and E13.5, covering proliferating and undifferentiated otic neuroblasts and differentiating VGNs and SGNs. We validate the high quality of our studies by using multiple assays, including genetic fate mapping analysis, and we uncover several genes upregulated in neuroblasts or differentiating VGNs and SGNs, such as Shox2, Myt1, Casz1, and Sall3. Notably, our findings suggest a general cascaded differentiation trajectory during early otic neurogenesis. The comprehensive understanding of early otic neurogenesis provided by our study holds critical implications for both basic and translational research.